Hypoglycemia Emergencies: Factors Associated with Prehospital Care, Transportation Status, Emergency Department Disposition, and Cost. (4th July 2019) - Kaufmann, Michael A.; Nelson, David R.; Kaushik, Puneet; Mann, N. Clay; Mitchell, Beth
Abstract: Objectives: The objectives of this study were to evaluate demographic/clinical characteristics and treatment/transportation decisions by emergency medical services (EMS) for patients with hypoglycemia and link EMS activations to patient disposition, outcomes, and costs to the emergency medical system. This evaluation was to identify potential areas where improvements in prehospital healthcare could be made.Methods: This was a retrospective analysis of the National Emergency Medical Services Information System (NEMSIS) registry and three national surveys: Nationwide Emergency Department Sample (NEDS), National Hospital Ambulatory Medical Care Survey (NHAMCS), and Medical Expenditure Panel Survey (MEPS) from 2013, to examine care of hypoglycemia from the prehospital and the emergency department (ED) perspectives.Results: The study estimated 270, 945 hypoglycemia EMS incidents from the NEMSIS registry. Treatments were consistent with national guidelines (i.e., oral glucose, intravenous [IV] dextrose, or glucagon), and patients were more likely to be transported to the ED if the incident was in a rural setting or they had other chief concerns related to the pulmonary or cardiovascular system. Use of IV dextrose decreased the likelihood of transportation. Approximately 43% of patients were not transported from the scene. Data from the NEDS survey estimated 258, 831 ED admissions for hypoglycemia, and 41% arrived by ambulance. The median ambulance expenditure was 664 ± 98. From the ED, 74% were released. The average ED charge that did not lead to hospital admission was 3106 ± 86. Increased odds of overnight admission included infection and acute renal failure.Conclusions: EMS activations for hypoglycemia are sizeable and yet a considerable proportion of patients are not transported to or are discharged from the ED. Seemingly, these events resolved and were not medically complex. It is possible that implementation and appropriate use of EMS treat-and-release protocols along with utilizing programs to educate patients on hypoglycemia risk factors and emergency preparedness could partially reduce the burden of hypoglycemia to the healthcare system.